2018
DOI: 10.1186/s12944-018-0848-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-HDL-cholesterol to HDL-cholesterol ratio is a better predictor of new-onset non-alcoholic fatty liver disease than non-HDL-cholesterol: a cohort study

Abstract: BackgroundThe nonHDLc/HDLc ratio (in which nonHDLc is defined as total cholesterol minus HDLc) is positively associated with multiple dyslipidemia-related disorders. This study aimed to determine whether the nonHDLc/HDLc ratio is an independent predictor of new-onset NAFLD (non-alcoholic fatty liver disease) in Chinese population.MethodsA perspective cohort study consisting of 3374 Chinese adults without liver diseases or metabolic disturbances was performed. Anthropometric parameters and data of metabolic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…According to the existing study, the NHDLC/HDLC ratio is better than NHDLC in predicting the occurrence of CVD in type 2 DM [10], and the ratio exhibits a higher prediction result than the apoB/apoA1 ratio of the IR and MS [9]. Moreover, as revealed from a perspective cohort study, the NHDLC/HDLC ratio outperforms NHDLC in predicting new-onset NAFLD in Chinese adult population [11]. Therefore, it is necessary to explore the association between the NHDLC/HDLC ratio and NAFLD in the pediatric population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the existing study, the NHDLC/HDLC ratio is better than NHDLC in predicting the occurrence of CVD in type 2 DM [10], and the ratio exhibits a higher prediction result than the apoB/apoA1 ratio of the IR and MS [9]. Moreover, as revealed from a perspective cohort study, the NHDLC/HDLC ratio outperforms NHDLC in predicting new-onset NAFLD in Chinese adult population [11]. Therefore, it is necessary to explore the association between the NHDLC/HDLC ratio and NAFLD in the pediatric population.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, NHDLC/HDLC ratio has a better predictive value for CVD in Type 2 DM than high-density lipoprotein cholesterol (HDLC) [7][8][9][10]. A recent prospective study found that the NHDLC/HDLC ratio is more sensitive to predict NAFLD in adults than non-high-density lipoprotein cholesterol (NHDLC) [11].…”
Section: Introductionmentioning
confidence: 99%
“…[15]. A perspective cohort study including 3374 Chinese adults investigated the association between nonHDL-C/HDL-C with NAFLD, with AUROC of 0.717 in women and 0.682 in men [28]. The Jinchang Cohort study consisting of 32,121 subjects, evaluated the ability of TC/HDL-C for identifying NAFLD, and the results suggested the AUC of TC/HDL-C was 0.645 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies reported that non-HDL-c/HDL-c rate more effectively predicts CVD in type 2 diabetes than non-HDL-c [11], and the ratio exhibits higher predictive value than the apoB/apoA1 rate in terms of insulin resistance and MS [8]. Moreover, as revealed from a perspective cohort study, non-HDL-c/HDL-c rate outperforms non-HDL-c in predicting new-onset NAFLD in Chinese adult population [11]. Thus, the associations of the non-HDL-c/HDL-c rate and the risk of NAFLD among children and adolescence should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, The non-HDLc/HDL-c rate is an independent risk factor of chronic kidney disease and gallbladder polyp, and it is an ideal marker for insulin resistance and metabolic syndrome [8][9][10]. As revealed from a perspective cohort study, non-HDL-c/HDL-c rate can more noticeably predict new-onset NAFLD than Non-HDL-c among adults [11]. However, the association between the non-HDL-c/HDL-c ratio and NAFLD among pediatric population remians unknown.…”
Section: Introductionmentioning
confidence: 99%